The Waziristan complex: some more chemical data and their interpretation - Hamidullah, Syed (Journal of Himalayan Earth Sciences, 1994)
Tholeiitic and calcalkline affinities are reflected by two different sets of rocks from the Waziristan island arc in 22 major element rock analyses. Previously published clinopyroxene analyses are used for comparison. The data confirms the existence of a fossil island arc in Waziristan.